Trainer Interaction Can Improve Welfare Outcomes of Toy Enrichment for Isolated Animals: A Case Study - Kelly Jaakkola; Sarah Brignac; Linda Erb; Emily Guarino; Abigail Haddock; Armando Rodriguez (Journal of Zoological and Botanical Gardens, 2023)
In cases where social animals must be temporarily housed alone, environmental enrichment is particularly important. Providing animals with manipulable objects (“toys”) is a common form of environmental enrichment, but its effectiveness can be limited by animal disinterest or habituation. The current study examined whether caregiver interaction could increase the effectiveness of object-based enrichment for a quarantined bottlenose dolphin (Tursiops truncatus). Behavioral observations were conducted after a training session, after a trainer toy play session, and between interactive sessions. The results showed that the dolphin floated in place less and played with toys more after interacting with a caregiver than he did at times further removed from caregiver interaction. He was also more likely to play with the same toys that the trainer had played with, showing effects of stimulus enhancement and/or social referencing. Although this study is, of necessity, based on a single animal of a single species, these findings suggest that interacting with a caregiver can enhance the efficacy of object-based environmental enrichment for isolated animals.